Fear factor. - Croser, Joe (Architects' Journal, 2003)
Evaluates the security risks of computer-aided design (CAD) technology. Security risk of CAD-data sharing; Capabilities of the CADSafe tool from DocumentFlow to reduce security risk of CAD-data sharing; Information on the CADSign tool.